Additive manufacturing – driving massive disruptive change in supply chain management. Issue 2 (6th July 2020) - Meier, Klaus-Jürgen
Abstract : Purpose: There are many academic contributions dealing with the impact of additive manufacturing on supply chains (Ben-Ner and Siemsen, 2017; Durach, 2017; Gravier and Roethlein, 2018; Brown, 2018; Rogers et al., 2016; Sasson and Johnson, 2016; Nyman and Sarlin, 2014). But how future supply chain design may differ from today is still vague. In this article, possible scenarios are discussed and decision support is provided for the management, which is responsible for long-term strategic decisions. Design/methodology/approach: This papers introduces the general characteristics of additive manufacturing and its next steps of development. Based on these technological assumptions various scenarios are systematically derived applying the standardized nomenclature of SCOR-model. Resulting threats and chances will be discussed and finally brought to a conclusion. Findings: With the spread of additive manufacturing, the industry has the opportunity to pursue completely new approaches in terms of product development, design and product properties. This not only leads to new competitive models and the possibility of customer individualization of the products down to volume "1". In addition, there are new models for supply chain management that can be used to react quickly and flexibly to customer requests. Already today new approaches for the cooperation between partners play an essential role.For start-ups, market entry should be simplified by using the resulting opportunities. Research limitations/implications: Future developments and especially the development speed of additive manufacturing are not predictable. Therefore, the expected scenarios may differ from reality and lead to a different supply chain design. There will also be industries that can use additive manufacturing much more intensively than others – not least because of the technological restrictions of the manufacturing process. Corporate culture and the overcoming of technical challenges are a decisive factor. Practical implications: This paper gives supply chain management an outlook on future development opportunities. This enables management to set the right course for a future-oriented position today. Social implications: The changes in the supply chain will open up new business models while existing models will disappear. This leads to a change in the field of logistics but also for many technology providers. As a consequence, there will be serious changes (opportunities and risks) for the employees involved and their working environment. Originality/value: This paper enables management to understand the scope and impact of upcoming changes. In this way, it significantly promotes awareness-raising and contributes to the future-oriented proceeding of companies.